Utility of the oxygen pulse in the diagnosis of obstructive coronary artery disease in physically fit patients. Issue 21 (12th November 2021) - Petek, Bradley J.; Churchill, Timothy W.; Sawalla Guseh, J.; Loomer, Garrett; Gustus, Sarah K.; Lewis, Gregory D.; Weiner, Rory B.; Baggish, Aaron L.; Wasfy, Meagan M.
Abstract: Cardiopulmonary exercise testing (CPET) guidelines recommend analysis of the oxygen (O2 ) pulse for a late exercise plateau in evaluation for obstructive coronary artery disease (OCAD). However, whether this O2 pulse trajectory is within the range of normal has been debated, and the diagnostic performance of the O2 pulse for OCAD in physically fit individuals, in whom V ˙ O 2 may be more likely to plateau, has not been evaluated. Using prospectively collected data from a sports cardiology program, patients were identified who were free of other cardiac disease and underwent clinically‐indicated CPET within 90 days of invasive or computed tomography coronary angiography. The diagnostic performance of quantitative O2 pulse metrics (late exercise slope, proportional change in slope during late exercise) and qualitative assessment for O2 pulse plateau to predict OCAD was assessed. Among 104 patients (age:56 ± 12 years, 30% female, peak V ˙ O 2 119 ± 34% predicted), the diagnostic performance for OCAD (n = 24, 23%) was poor for both quantitative and qualitative metrics reflecting an O2 pulse plateau (late exercise slope: AUC = 0.55, sensitivity = 68%, specificity = 41%; proportional change in slope: AUC = 0.55, sensitivity = 91%, specificity = 18%; visual plateau/decline: AUC = 0.51, sensitivity = 33%, specificity = 67%). When O2 pulse parameters were added to the electrocardiogram, the change in AUC was minimal (−0.01 to +0.02, p  ≥ 0.05). Those patients without OCAD with a plateau or decline in O2 pulse were fitter than those with linear augmentation (peak V ˙ O 2 133 ± 31% vs. 114 ± 36% predicted, p  < 0.05) and had a longer exercise ramp time (9.5 ± 3.2 vs. 8.0 ± 2.5 min, p  < 0.05). Overall, a plateau in O2 pulse was not a useful predictor of OCAD in a physically fit population, indicating that the O2 pulse should be integrated with other CPET parameters and may reflect a physiologic limitation of stroke volume and/or O2 extraction during intense exercise. Abstract : Cardiopulmonary exercise testing (CPET) guidelines recommend analysis of the oxygen (O2 ) pulse for a late exercise plateau in evaluation for obstructive coronary artery disease (OCAD). The diagnostic performance of the O2 pulse for OCAD in physically fit individuals, in whom V ˙ O 2 may be more likely to plateau, has not previously been evaluated. We found that a plateau in O2 pulse was not a useful predictor of OCAD in a physically fit population and may reflect a physiologic limitation of stroke volume and/or O2 extraction during exercise rather than a pathologic fall in stroke volume due to ischemia.